Autonomy and intimacy in the family as risk factors for sexual abuse - Tanja Repič (Psihološka Obzorja, 2006)
The study examined the level of two risk factors (autonomy and intimacy) for healthy functional family among sexually abused and sexually non-abused individuals. Autonomy and intimacy were measured with Family-of-Origin Scale (FOS; Hovestadt, Anderson, Piercy, Cochran, & Fine, 1985). 261 participants (194 girls and 67 boys) completed the FOS, average age was 25 years (SD = 7). Among all participants 18% were sexually abused (N = 46), approximately every fifth (5.7) girl and every seventh (6.7) boy. There were 78% girls and 22% boys among sexually abused participants. Families of sexually abused participants in comparison with the families of sexually non-abused showed many statistically significant differences in elements of autonomy (clarity of expressing emotions, responsibility, respect for others, openness to others, and acceptance of separation and loss) and intimacy (encouraging expression of a range of feelings, creating a warm atmosphere in the home, dealing with conflict resolution without undue stress, promoting empathy among family members, trust and developing trust). In general the sexually abused group had a statistically significantly lower level of autonomy and intimacy in comparison with sexually non-abused group.